Mengurai Gagasan Tan Malaka sebagai Bentuk Kontribusi Terhadap Pemerintah Republik Indonesia - Raden Samidi; Suharno Suharno (Forum Ilmu Sosial)
The purpose of writing this article is to unravel the ideas of Tan Malaka as a form of contribution to the government of the Republic of Indonesia. The type of writing of this article uses the study of literature by exploring each of Tan Malaka's ideas from several of his work books as objects of study and supported by several other works of books, then analyzed inductively. Based on the results of the study, it shows that every revolutionary idea of Tan Malaka has a real contribution in his relationship to build citizens and the state, both seen from the context of nationalism, economy, politics, and human rights. Through Citizenship Education, it is fitting that Tan Malaka be placed on an equal footing with the founders of the Indonesian nation in the hope that every idea contained in his work will be used as a reference to build a better nation in the future.